Carotenoids: their sources, bioactivity, and application in industry - Jaswir, Irwandi; Noviendri, Dedi; Md Aris, Mohd Aznan; Ismail, Soraya; Lestari, Widya; Mat Harun, Noraihan; Hendri, Ridar (Wiley, 2024)
Carotenoids are ubiquitous natural pigments found in confer red, orange, and yellow colors to various organisms in the plant and animal kingdoms (Basu et al. 2001; Sugawara et al. 2009). Over 700 naturally occurring pigments found in higher plants and animals are classified as carotenoid compounds (Godinho and Bhosle 2008; Konishi et al. 2008). Plants, algae, fungi, and bacteria biosynthesize carotenoid pigments de novo, while animals are unable to biosynthesize carotenoids, instead obtain them from their diet (Okada et al. 2008; Rock 1997). The carotenoids give color to different parts of the plants, such as flowers, leaves, and fruits (Mattea et al. 2009), and in animals, such as the muscles and feathers of certain animals (Mortensen 2006). In plants, microorganisms, and animals, carotenoids accumulate in the cells where they not only impart color, but also exert important bioactivity (Fujisawa et al. 2008). Carotenoids are made up of approximately 40 carbon atoms of 8C5 isoprene units connected from head to tail (Bonnie and Choo 1999; Mattea et al. 2009). Biosynthesis of carotenoid begins with the addition of C5 isoprenoid units to form a C20 long chain, which undergoes dimerization to form a C40 carotenoid. This basic structure then undergoes various modifications, such as cyclization, dehydrogenation, rearrangement, oxidation, and epoxidation, giving rise to various other carotenoid chemical structures (Figure 11.1) (Yano et al. 2005). The two major groups of carotenoids are carotenes and xanthophylls, divided according to their chemical structure (PerezRodrıguez 2009). The carotenes such as α-carotene, β-carotene, and lycopene are devoid of any oxygen molecules and consist solely of hydrocarbons, while xanthophylls such as lutein, fucoxanthin, astaxanthin, and zeaxanthin contain oxygenated molecules such as hydroxyl, methoxy, carboxyl, keto, and epoxy groups (Aizawa and Inakuma 2007; Britton 1995;Perez-Rodrıguez 2009). All carotenoids contain conjugated double bonds arranged in a long chain with acyclic or cyclic substituents in their structure (Stahl and Sies 2007). Figure 11.2 shows the chemical structures of carotenes and xanthophylls. Carotenoids not only give plants and animals their vibrant colors (Aoki et al. 2002), but also have important physiological functions in the organism (Umeno et al. 2005). Both photosynthetic and non-photosynthetic organisms have been reported to synthesize carotenoids in their cells, resulting in their various shades of color ranging from yellow to red (Misawa 2009). In plants, carotenoids facilitate photosynthesis, prevent light oxidation, protect the plant from high amounts of light and oxidative damage during light harvest (Demmig-Adams and Adams III 2002), and regulate the fluidity of the cell lipid bilayer (Umeno et al. 2005). Their ability to absorb light is attributed to the multiple conjugated double bonds in their chemical structure, which carry cyclic or acyclic groups (Stahl and Sies 2007).